SENTIMENT ANALYSIS ON SOCIAL MEDIA: HATE SPEECH TO THE GOVERNMENT ON TWITTER - Anwar Sadat; Herman Lawelai; Ansar Suherman (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to determine public sentiment towards hate speech against the government on Twitter social media. This study analyzes and uses data available on Drone Emprit Academic. This study analyzed a total of 1,088 tweets collected on Twitter with the tweet “Hate Speech Kepada Pemerintah”. The results of this study indicate that the public's response to hate speech against the government during September 1 to December 31, 2021 is positive with 67% responding positively, 31% responding negatively, and the remaining 1% responding neutrally. Thus, government policies are needed to protect freedom of expression as a very basic human right while at the same time limiting the spread of hate speech. The role of law enforcement in fighting hate speech is critical, but it is not the only option.